Potensi Bahan Baku Produk Pangan Darurat di Asia Tenggara: Potential Raw Materials for Emergency Food Products in Southeast Asia - Resti, Nina; Ayustaningwarno, Fitriyono; Anjani, Gemala; Syauqy, Ahmad; Nuryanto, Nuryanto; Chasanah, Ekowati; Purwani, Endang Yuli; Zhu, Fan; Afifah, Diana Nur (Universitas Airlangga, 2025)
Background: The occurrence of natural disaster in Southeast Asia due to its location along the Asia Pacific Ring of Fire is high. The consequences of the natural disasters on various aspects, like that social, financial, and food security can be large. This initiative promotes the development of emergency food products to address the daily nutritional requirements of natural disaster victims, ensuring their survival. The specified standard is 2,100 kcal/day, emphasizing a balanced distribution of macronutrients (40-50% carbohydrates, 35-45% fat, and 10-15% protein). Objectives: This literature review explored the potential raw materials for emergency food products in the Southeast Asia. Methods: This review utilized databases from Google Scholar and PubMed websites, employing specific keywords for each identified category to gather the latest literature. The literature obtained was 10 article. Discussions: This review explores solutions to the challenges posed by natural disasters in Southeast Asia, focusing on the potential use of locally available resources as raw materials for emergency food products. Raw materials, including Fish Hydrolyzate Protein (FPH), offer numerous benefits due to their bioactive contents, such as antioxidant, antihyperglycemic, antimicrobial, antitumor, ACE inhibitor activity, calcium binding, and anticoagulant properties, particularly beneficial for vulnerable groups. The review also delves into the elimination of raw materials, the nutritional content of various types of emergency food products, and innovative solutions for emergency food products in Southeast Asia. Conclusions: The potential raw materials identified have the capability to yield innovative emergency food products with both excellent physicochemical quality and health potential.